Spin-state engineering of cobalt(IV)-oxo enables direct oxygen atom transfer for high-efficiency olefin epoxidation - Xue Li; Yufan Zhang; Jie Yang; Jikun Li; Xiaohui Wang; Tiantian Chen; Guangming Zhan; Chuncheng Chen; Mingce Long; Lizhi Zhang (Proceedings of the National Academy of Sciences, 2026)
High-valent metal-oxo species, such as cobalt(IV)-oxo (Co IV =O) complexes, represent promising candidates for catalytic olefin epoxidation via oxygen atom transfer (OAT) under mild conditions. However, their utility is often limited by radical-mediated side reactions stemming from stepwise electron-transfer mechanisms. Here, we report a strategy to circumvent this limitation by modulating the spin state of the Co IV =O center through geometry-mediated ligand-field adjustment. Specifically, we employ a planar tricoordinated cobalt site to activate peroxymonosulfate (PMS), generating an intermediate-spin Co IV =O species ((O 3 )Co IV =O, S = 3/2). Unlike its planar tetra-coordinated low-spin counterpart ((O 4 )Co IV =O, S = 1/2), the weakened equatorial coordination field in this configuration reduces the crystal-field splitting energy and rearranges orbital energy levels, stabilizing the empty σ* (d z 2 -p z ) orbital at a lower energy level, enabling direct transfer of a π-electron pair from the olefin substrate. Consequently, the OAT mechanism shifts from a stepwise single-electron transfer to a concerted two-electron pathway, bypassing radical intermediate formation and enhancing both reactivity and selectivity. In the epoxidation of trans-stilbene and derivatives, the (O 3 )Co IV =O catalyst achieves up to 89.2% conversion with 99.9% selectivity, substantially outperforming conventional noble-metal-based systems. Our findings underscore the critical role of spin-state control in promoting concerted OAT and open avenues for designing next-generation oxidation catalysts.